A Critical Study of Contracts in the Perspective of Fiqh Mu’amalah (Overview of Contract Defects) - fahmi irfanudin (ITB AAS INDONESIA Surakarta, 2023)
The scope of mu’amalah law is very broad and varied. And among the scope of muamalah law, especially with regard to muamalah maliyyah, is a contract. The contract is a logical consequence of social relations in human life. Where in carrying out their activities in life in this world, humans are required to interact with one another in order to meet their needs, and the contract is one of the legally justified ways of obtaining ownership. The contract can occur after an agreement process between two parties to transfer property rights from one party to another, for example, in buying and selling transactions, renting, and so on. The following article aims to discuss more specifically the defects that occur in the contract from the perspective of Fiqh Mu'amalah since a transaction sometimes contains several defects that can cause the contract to be considered invalid or to be fasakh (canceled). This qualitative research focused on literature research with descriptive-analytical nature based on the study of the text. In this case, the book Fiqh Mu'amalah with the theme of defective contracts, acts as primary data. The research data was collected by the documentation method, then analyzed using qualitative analysis. The results of this study indicate that there are several defects in the contract which have implications for the defect of the contract, or at least the contract can be canceled (fasakh), including tadlis (cheating), ghalath (error), ikrah (coercion), ghabn (hidden price), gharar (betting and obscurity), and jahalah (ignorance).